Sustainability management of jet engine repair business: How component repairs benefit the aerospace industry - Cederberg, Line; Hæstad Bjørnstad, Victoria (My University, 2023)
Climate transition in industry has received a lot of attention and research the last years and the aerospace industry is no exception. The industry has a reputation to be a contributor to global emissions and holistic changes are needed to achieve long-term economic and environmental sustainability. The regularly maintenance and repair of jet engines have created a considerable aftermarket. However, little empirical research on the sustainability impact of engine repair has been done. The study aims to investigate economic and environmental sustainability of a parts repair business in the aerospace industry. Literature, interviews and internal documents laid the foundation for mapping and calculating environmental and financial impact of the activities. Subsequently, the results was put in relation to literature on the topic of life cycle management, technological cycles, sustainable business model and stakeholders to assess the strategic portfolio. Main findings are that repair has considerable positive environmental impact, yet being cost efficient, which creates economic opportunities for the case company. However, the environmental impact differs between repair methods, where additive manufacturing proved to be the most environmental sustainable. Further, the study claims that distributing the benefits between stakeholders is essential for a viable business model innovation.
Keywords: life cycle management; environmental management; sustainable business; sustainable business innovation; MRO; aerospace industry; jet engine repair; technological cycles